Improving Students' Vocabulary Ability: Teacher Planning Strategies in English Language Teaching - Aulia Yunus; Ayumi Seftina; Dwi Fatimah; Namira Syaharani; Khairunnisa Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to explore the planning strategies implemented by teachers in improving students' vocabulary skills in teaching English. Vocabulary is an important component in language learning which influences students' communication skills and text comprehension. This research analyzes the various approaches used by teachers to develop students' vocabulary, as well as the challenges faced in planning and implementing these strategies in the classroom. Data was obtained through interviews with teachers, classroom observations, and analysis of learning implementation plan (RPP) documents. The research results show that strategies such as the use of visual media, contextual teaching, and regular repetition of vocabulary have proven effective in improving students' vocabulary skills. In addition, the teacher's role in creating an environment that supports vocabulary learning is very important in helping students master new words. This research provides insight for English teachers in planning more effective and innovative teaching to improve students' vocabulary skills.